Pendidikan Islam STRATEGI PEMBELAJARAN DENGAN MENGGUNAKAN PENDEKATAN PEMBELAJARAN BERBASIS OUTCOME BASED EDUCATION - ummu kulsum (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2021)
Strategy is a step to prepare a program or concept so that what has been planned works well in accordance with the desired goals. Likewise, in the learning strategy in managing the classroom, several approaches are needed, including the behavior modification approach, the emotional social climate approach, the group process approach and the eclectic approach. Some of these approaches need to be adapted to the desired subjects, for example Islamic religious education subjects, so a learning strategy is needed using an approach from one of the several approaches. To maximize the achievement of the final results of the learning process in the classroom, use outcome based education (OBE), because the ultimate goal of this OBE is that students are guided to have competencies and skills in accordance with the cognitive, affective and psychomotor domains in classroom learning.